2016
DOI: 10.1177/0011128715575141
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Adult Under- and Over-Reporting of Self-Reported Arrests From Discrepancies in Adolescent Self-Reports of Arrests

Abstract: Building on previous research, this article investigates whether discrepancies between official and self-reported measures of arrests as an adult can be predicted from such discrepancies as an adolescent. We use longitudinal data from the Rochester Youth Development Study to assess whether a pattern exists in adolescent and adult under-and over-reporting of arrests. We find consistency in under-and over-reporting throughout the adolescent-young adult life course. In other words, when respondents misreport the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
(41 reference statements)
1
5
0
Order By: Relevance
“…This result generally agreed with Krohn et al (2013) finding that a higher number of officially reported arrests was correlated to a higher error in self-reported arrests (due to a systematic relationship); however, Emmert et al (2015) noted that young adults tend to be more predictable even though under-and over-reporting of arrests exist on a continuum from adolescence to young adulthood.…”
supporting
confidence: 85%
See 2 more Smart Citations
“…This result generally agreed with Krohn et al (2013) finding that a higher number of officially reported arrests was correlated to a higher error in self-reported arrests (due to a systematic relationship); however, Emmert et al (2015) noted that young adults tend to be more predictable even though under-and over-reporting of arrests exist on a continuum from adolescence to young adulthood.…”
supporting
confidence: 85%
“…The consistency between self-reported arrests and officially-recorded arrest data has been given some attention (Emmert, Carlock, Lizotte, & Krohn, 2015;Hindelang et al, 1981;Kirk, 2006;Krohn, Lizotte, Phillips, Thornberry, & Bell, 2013;Maxfield et al, 2000;Piquero et al, 2014;Thornberry & Krohn, 2003); however, those studies have primarily looked at the consistency and validity between self-reported arrest and officially-recorded arrests. Generally, the results have shown moderate to strong consistency between self-reported arrest and officially-recorded arrests with some differential validity across gender and/or race.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, this study is limited by its use of self-report data to measure justice system involvement. Although self-reports of justice system involvement are generally accurate, responses may be less accurate for individuals with frequent justice system contact (Emmert, Carlock, Lizotte, & Krohn, 2017; Piquero, Schubert, & Brame, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Both sources of data are valid proxies of an individual's antisocial history, however. Despite the potential differences in these sources of data, there nevertheless is evidence that they substantially overlap and the overlap is often moderate to strong (Emmert et al, 2015;Hindelang et al, 1979;Huizinga and Elliott, 1986;Maxfield et al, 2000;Piquero et al, 2014;Sutton et al, 2011;Thornberry and Krohn, 2000). For instance, a recent study of self-reported vs official recorded arrests using data from the National Youth Survey Family Study found that self-reported and official records of arrest were concordant for more than 80 percent of offenders (Pollock et al, 2015).…”
Section: Introductionmentioning
confidence: 99%